The Role of Anging Mamiri Women's Solidarity Community in Empowering Marginalized Women in Makassar City - Mariati Rahman; Tahir Malik; Nisma Arishka Masdar (PT Publikasiku Academic Solution, 2023)
This study aims to explain the implementation of the Anging Mammiri Women's Solidarity program in Makassar City, the type of descriptive qualitative research, collecting and analyzing data applied triangulation, namely interviews, observations, and document reviews. Information was gathered from informant interviews and documents reviewed. The results showed that as many as 142 marginalized (poor) women had received services or advocacy in the form of education, information, and communication. The number of violence against women and children in the city of Makassar reached 1,056 people. (in 2022) As many as 774 children who were victims of violence, and 184 victims of domestic violence (domestic violence), 98 children facing the law, educational qualifications were dominated by children with junior high school and high school education. The number of violence against women who do not want their land to be confiscated is 111 structural cases and 126 non-structural cases, namely in the agrarian sector, forestry, infrastructure development, and property business. The implementation of the program has not been carried out optimally, because the number of personnel/members is less when compared to the number of marginalized people who need services. The factors that support the implementation are the determination and very high concern of the persons/members of SPAM.